(untitled) (Journal of Fatima Jinnah Medical University, 2020)
Background: Central serous chorioretinopathy (CSCR) is an idiopathic disorder in which there is leakage of fluid from hyper permeable choriocapillaris and the collection of fluid between neurosensory and neuropigmentry retina in the macular area that is responsible for decrease visual acuity. CSCR may be acute or chronic. Various treatment options include simple observation, argon laser photocoagulation of the leaking spot, photodynamic therapy (PDT), oral ketoconazole and oral rifampicin are available. Ranibizumab is a monoclonal antibody fragment that act as vascular endothelial growth factor inhibitor, stabilize blood retinal barrier and decrease leakage from choriocapillaris. This study aims to evaluate the role of intravitreal ranibizumab for rapid recovery in central serous chorioretinopathy. Patients and methods: This descriptive case series was carried out at Department of Ophthalmology, Nishtar Medical University Multan, Pakistan from 01-10-2019 till 30-04-2020. The study included twelve eyes of twelve patients suffering from acute CSCR. All patients were given a single injection of intravitreal ranibizumab (0.5mg/0.05ml) as a primary treatment and followed for two months after injection at one week, one month and two months interval to document efficacy of intravitreal ranibizumab. At each baseline and follow up visits, dilated fundus examination was carried out, ending up with patients’ best corrected visual acuity. Central retinal thickness (CRT) was also recorded and results were compared with prior visit results of patients. Major outcomes were the improvement in visual acuity and decrease in CRT. Baseline CRT values were also compared with post injection CRT values at one week, one month and two months intervals using paired sample t-test and best corrected visual acuity (BCVA) was compared using chi–square test. Results: Mean age of the patients was 39.6 years with a male to female ratio of 9:1. Best corrected visual acuity was 6/60 on Snellen chart at baseline. All patients exhibited mean improvement of best corrected visual acuity of three Snellen lines after one week. Eleven patients were back to best corrected visual acuity of 6/6 after one month. Remaining one patient gained best corrected visual acuity of 6/6 after two months of post injection. The mean CRT at presentation was 500 ± 80U (range; 386–580) which reduced significantly to 272 ± 52 U (range 220–338) from baseline after one month showing significant reduction (p<0.001). At the last follow-up visit, the CRT was measured 230 ± 20 U (range 220—250) which shows complete resolution of sub-retinal fluid. Conclusion: Intravitreal ranibizumab can be used for rapid absorption of sub-retinal fluid in acute CSCR and significant reduction in CRT along with improvement in BCVA indicate that it may be safely employed in CSCR to achieve better clinical outcomes.